Pregnancy preeclampsia: the main stages of pathogenesis. An infuence into fetal organogenesis (literature review) - Poliasnyi, V. O.; Kupriianova, L. S. (Journal of Education, Health and Sport, 2021)
In the current article there is observed a serious problem of the development of preeclampsia (PE) at a level of severity among women in Ukraine. It is disassembled in the description of the main theories of the development of PE: allergic, hormonal and renal. So that it can be instilled in some types of diseases and the theory of cortical-visceral ailments, which is leading on the pink modern data. The study of cephalic changes to the pathogenesis of PE made it possible to see and describe the peculiarities of the structure of the placenta’s vessels with this pathology with an eye on the development of endothelial dysfunction; hormone-stimulating activity in the mother - placenta - fetus system. Statistically, persons are indicated in a hematoencephalic institution, they are seen in the organisms of fetuses from mothers from the stage of severity. All the above specialties are seen as far as the degree of severity of the PE. It has been shown that in fetuses from mothers and PEs in the later ontogeny, there may be a breakdown of the implementation and the main stages in the development of cells, uterus and uterine tubes. Moreover, there is a trend towards the development of the pathology of the organs of the statutory system in case of women, women of all types of mothers from the moderate and severe stage, as well as a great number of changes in the development of PE at a given birth.